1999
DOI: 10.1002/(sici)1097-0215(19990924)83:1<5::aid-ijc2>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 andBRCA2 genes: Role in hereditary breast and ovarian cancer in Italy

Abstract: The heritable defects of BRCA1 and BRCA2 genes have been shown to predispose to breast and ovarian cancers. In a previous report, we analyzed 46 Italian families with breast and/or ovarian cancer for BRCA1 mutations. In the present study, those families and 11 others were screened for BRCA2 mutations; the newly enrolled families were also analyzed for the BRCA1 gene. The coding region and splice boundaries of BRCA2 and BRCA1 genes were assessed by the protein‐truncation test and single‐strand conformational po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
2
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
(17 reference statements)
6
36
2
2
Order By: Relevance
“…16 In all of these studies, the highest frequencies of mutations were identified in family types corresponding to our Groups A and B. For both groups, higher mutation rates were detected in the BRCA1 gene.…”
Section: Frequencies Of Brca Mutations In German Families and Search mentioning
confidence: 68%
See 1 more Smart Citation
“…16 In all of these studies, the highest frequencies of mutations were identified in family types corresponding to our Groups A and B. For both groups, higher mutation rates were detected in the BRCA1 gene.…”
Section: Frequencies Of Brca Mutations In German Families and Search mentioning
confidence: 68%
“…[12][13][14][15] The proportion of cases attributed to BRCA1 ranges from 10% in Finland and the Netherlands to approximately 25% in France and Sweden, BRCA2 mutation detection rates are generally around 10%, with the exception of Italy where germline mutations have been found in 25% of 49 families analyzed. 16 There are to date no comprehensive studies in the German population where most studies have been limited to the analysis of BRCA1 or to relatively small series. [17][18][19][20] In 1996, the Deutsche Krebshilfe supported the formation of a research collaboration, the "German Consortium for Hereditary Breast and Ovarian Cancer," to establish a national network for the management and treatment of women with a familial predisposition to breast and ovarian cancer.…”
mentioning
confidence: 99%
“…This analysis allowed to detect eight different mutations, with a detection rate of 11.7%. In the two previous studies carried out in Italy by screening the entire BRCA1/BRCA2 sequences, Ottini et al (2000) detected mutations in 8% of 136 Italian patients, while Santarosa et al (1999) disclosed mutations in 37% of cases studying 57 selected Italian families. These different detection rates are clearly due to the different criteria of selection employed, since Santarosa et al (1999) used more stringent criteria of autosomal-dominant predisposition.…”
Section: Discussionmentioning
confidence: 87%
“…The availability of this highly recurrent mutation may also contribute to the elucidation of the molecular mechanisms responsible for the tissue specificity of particular cancer-linked mutations. The IVS16-2A4G mutation was reported worldwide only three times by the BIC database, twice by Myriad in 'Western Europeans' and once by Dr M Santarosa 13 from Aviano, a city located in Italy at less than 100 km from the Slovenian border. The eastern part of today's Italy and Slovenia were before the First World War part of the Austro-Hungarian empire, and there is still a Slovene minority officially recognized in the eastern part of Italy.…”
Section: Resultsmentioning
confidence: 99%